Hepatic epithelioid hemangioendothelioma with TFE3 rearrangement: a case report and literature review - Meng, Ke; Yang, Xingrong; Guo, Sitong; Tao, Juan (Frontiers in Oncology, 2025)
Epithelioid hemangioendothelioma (EHE) is a rare low-grade malignant tumor of vascular origin. It may be confusing as its manifestations of multifocal lesions on imaging and epithelial histomorphology in pathology. EHE is easy to be mistaken for a metastatic tumor by radiologists and clinicians. Correct diagnosis and therapy are important owing to the variable clinical course and special treatment. EHEs harbor major CAMTA1 rearrangement and <5% TFE3 rearrangement. Meanwhile, EHE with TFE3 rearrangement has distinctive morphology features. Currently, there are only two cases of hepatic EHE with TFE3 rearrangement reported, we present another case here that occurred in a 34-year-old female. Both the clinician and radiologist provisionally considered it as a metastatic tumor. The tumor cells have mild atypia but infiltrative growth patterns like benign vascular tumors. Our case is unique mainly in that the absence of its characteristic well-defined vessels, and the presence of unreported morphology of intraluminal papillary proliferation of tombstone or hobnail endothelial cells. The final diagnosis of EHE with TFE3 rearrangement was made by combining morphological, immunohistochemical, and molecular test results. The patient did not receive any treatment according to her condition and no change was detected in the mass’s size and number on CT images during 3.5 years of follow-up.